(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This article aims to discuss artistic investigations and the discovery of the puppet-body, crossing the text through notes and inquiry extracted from the author’s work diary from the activities of her Study Group. In 2019, the Group linked to the Master’s degree of Célia Helena Higher School of Arts examined the resignification of the body of the actor in puppet-body form mainly from the ningyō buri style of kabuki, inspired by the bunraku and the filmed stage show Drums on the dike of the Théâtre du Soleil. In conceptual terms, it dialogued with Meyerhold, Oida, Kusano and Greiner.